2018
DOI: 10.1111/cpf.12504
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow restriction and cuff width: effect on blood flow in the legs

Abstract: As long as relative pressures are applied, cuff width appears to have little to no effect on the blood flow stimulus during blood flow restriction at rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
3
18
2
Order By: Relevance
“…Our results for visit 1 show that the relationship between cuff-induced pressure and blood flow in the superficial femoral artery is nonlinear when measured in a seated position. This is contrary to the findings of Mouser et al (27), who reported a linear blood flow/pressure relationship in the posterior tibial artery, however, consistent with a previously reported (17) nonlinear blood flow/pressure relationship in the brachial artery. Both studies were performed in the supine position (17,27).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our results for visit 1 show that the relationship between cuff-induced pressure and blood flow in the superficial femoral artery is nonlinear when measured in a seated position. This is contrary to the findings of Mouser et al (27), who reported a linear blood flow/pressure relationship in the posterior tibial artery, however, consistent with a previously reported (17) nonlinear blood flow/pressure relationship in the brachial artery. Both studies were performed in the supine position (17,27).…”
Section: Discussioncontrasting
confidence: 58%
“…Measurement of AOP in the posterior tibial artery has been reported to increase from the supine to seated position (26). Arterial blood flow has been reported to decrease with increasing cuff pressure in a linear fashion in the posterior tibial artery in the supine position (27) as opposed to a nonlinear fashion in the brachial artery in a standing position (28). Further research is needed to determine if blood flow response in the lower extremities is linear or nonlinear in a seated position.…”
Section: Introductionmentioning
confidence: 99%
“…However, various moderator variables can influence the cuff pressure: Cuff width : wide BFR-cuffs restrict arterial blood flow more than narrow BFR-cuffs using the same cuff pressure. Therefore, the cuff pressure should be applied relative to the cuff width [ 214 , 215 , 218 , 219 , 220 , 221 , 222 ]. Cuff material : it might be that the cuff material has an impact on the arterial blood flow restriction [ 211 ].…”
Section: Resistance Training With Blood Flow Restriction—an Added mentioning
confidence: 99%
“…Cuff width : wide BFR-cuffs restrict arterial blood flow more than narrow BFR-cuffs using the same cuff pressure. Therefore, the cuff pressure should be applied relative to the cuff width [ 214 , 215 , 218 , 219 , 220 , 221 , 222 ].…”
Section: Resistance Training With Blood Flow Restriction—an Added mentioning
confidence: 99%
“…For example, individualized applied pressures during BFR exercise can be derived from measures of limb occlusion pressure (LOP) or arterial occlusion pressure (AOP), usually as a percentage of this value 15 . These individualized pressures are favorable when applying cuff pressure during BFR exercise, as they help address some of the variability in restriction caused by differences in the equipment used, such as differing cuff widths, when set at the same absolute pressure 16 . Still, only recently has research begun to define minimal threshold pressure ranges suitable to attain the relevant acute affects needed for muscular adaptation to BFR exercise 17 .…”
Section: Introductionmentioning
confidence: 99%